2018
DOI: 10.3389/fneur.2018.00357
|View full text |Cite
|
Sign up to set email alerts
|

Non-Motor Symptoms as Predictors of Quality of Life in Egyptian Patients With Parkinson’s Disease: A Cross-Sectional Study Using a Culturally Adapted 39-Item Parkinson’s Disease Questionnaire

Abstract: ObjectiveThe prevalence of non-motor symptoms (NMSs) and their impact on health-related quality of life (HRQoL) in Parkinson’s disease (PD) has been reported inconsistently among different populations. In this study, we aimed to investigate the NMSs and HRQoL profiles and their correlation in Egyptian PD patients, using a culturally adapted Arabic version of the 39-item Parkinson’s disease questionnaire (PDQ-39).MethodsNinety-seven PD patients were rated using the unified Parkinson’s disease rating scale (UPDR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
48
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 45 publications
(59 citation statements)
references
References 34 publications
11
48
0
Order By: Relevance
“…As in our study, other findings showed that there is a correlation between the motor and non-motor symptoms [15][16].…”
Section: Resultssupporting
confidence: 86%
“…As in our study, other findings showed that there is a correlation between the motor and non-motor symptoms [15][16].…”
Section: Resultssupporting
confidence: 86%
“…8,9 Interestingly, similar non-motor profile was detected in Egyptian PD patients. 30 On the other hand, other previous studies used the non-motor symptoms questionnaire (NMSQuest) and/or compared patients of ET to PD patients. An epidemiological survey of Chinese populations reported NMSs among ET patients, similar to normal controls, except higher frequency of restless legs.…”
Section: Discussionmentioning
confidence: 99%
“…NMSs were present in 96.4% of the studied patients by Khedr et al [4] with mood and cognitive dysfunction as the most common followed by sleep disturbance and fatigue. In another Egyptian study by Shalash et al [5], all studied patients had one or more NMSs, with the most common were fatigue and sleep disturbance.…”
Section: Introductionmentioning
confidence: 93%